Consistency of Children’s Emotions Through Water Play Activities Group A - Irawati Irawati; Abdul Muiz Rouf; M Arif Syarif H (FKIP - Universitas Riau, 2026)
Emotional consistency is an important aspect of early childhood social emotional development that needs to be stimulated through meaningful learning experiences. However, many children still experience difficulties in controlling and expressing their emotions appropriately during classroom activities. Therefore, learning activities that involve sensory experiences are needed to help children develop better emotional regulation. This study aimed to improve the emotional consistency of early childhood through water play activities using bubble water media. The research employed a classroom action research design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The participants of this study were children in early childhood education. Data were collected through observation, interviews, and documentation, and were analyzed descriptively to examine the changes in children’s emotional behavior during the learning process. The result of study showed that the implementation of water play activities encouraged children to practice patience, follow play rules, and interact positively with peers. These activities also provided calming sensory stimulation that helped children regulate their emotional responses. In conclusion, water play activities using bubble water media can serve as an effective play based learning strategy to support the development of emotional consistency in early childhood.